Knockdown of NtCPS2 promotes plant growth and reduces drought tolerance in Nicotiana tabacum - Xu, Shixiao; Han, Wenlong; Cao, Kexin; Li, Bo; Zheng, Cong; Xie, Ke; Li, Wei; He, Lingxiao (Frontiers in Plant Science, 2022)
Drought stress is one of the primary environmental stress factors that gravely threaten crops growth, development, and yields. After drought stress, plants can regulate the content and proportion of various hormone to adjust their growth and development, and in some cases to minimize the adverse effects of drought stress. In our previous study, the tobacco cis-abienol synthesis gene (NtCPS2) was found to affect hormone synthesis in tobacco plants. Unfortunately, the role of NtCPS2 genes in abiotic stress response is yet to be studied. Here, we present data supporting the role of NtCPS2 genes in drought stress and possible underlying molecular mechanisms. The NtCPS2 gene expression levels were induced by polyethylene glycol, high-temperature, and virus treatments. Subcellular localization results indicated that NtCPS2 was localized in the cell membrane. The NtCPS2-knockdown plants exhibited higher levels of gibberellin (GA) content and synthesis pathway genes expression but lower abscisic acid (ABA) content and synthesis pathway genes expression in response to drought stress. In addition, the transgenic tobacco lines exhibited higher leaf water loss and electrolyte leakage, lower content of soluble protein and reactive oxygen species (ROS), and lower antioxidant enzyme activities after drought treatment when compared with wild type (WT) plants. In conclusion, NtCPS2 positively regulates drought stress tolerance possibly by modulation of the ratio of GA to ABA, which was verified by the detection of related phenotypic and physiological indicators. This study may provide evidence for the feedback regulation of terpenoids to abiotic and biotic stresses.